Controle da extrafiscalidade à luz da igualdade: limitações ao poder de desonerar e soluções jurisdicionais para correção de situações antiisonômicas - Fernandes, Rayneider Brunelli de Oliveira (2014)
The theme of extrafiscality underlies a lot of political, legal and economic issues. In the Law, it‟s questioned the possibility of relativizing the ability to pay through the forceful use of taxes for purposes other than the collection. In the jurisprudence of the brazillian Supreme Court, this debate tending to establish limits on extrafiscality is still incipient, figuring obscure the freedom of the legislature to build his economic policies. In this pillar, it attempted to build, through the bibliographical and documental research, a proposal that addresses the control parameters of extrafiscal measures‟ validity using the tools available to the juridical system. By the hypothetical-deductive method, it is argued that any measure that imports the relativisation of the fundamental right to equality marked by the ability to pay needs to be grounded in the Constitution and be rationally justified by the legislature. The legislative partial omissions, which are the major challenge in the harvest of the effectuation of equality, are not credited as immune from judicial review, deserving customized legal solutions in order to harmonize the principles of fair taxation due to budgetary legal certainty.